ANALISIS KUALITAS LAYANAN JARINGAN 4G LTE MENGGUNAKAN METODE WALK TEST DAN PENGUKURAN QOS (QUALITY OF SERVICE) DI SAMARINDA CENTRAL PLAZA - Tri Duwi Pramudito; Wawan Joko Pranoto; Abdul Hallim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the quality of 4G LTE network services at Samarinda Central Plaza (SCP) using the Walk Test method and Quality of Service (QoS) measurements for three major providers: Telkomsel, XL Axiata, and Indosat. Measured parameters include Reference Signal Received Power (RSRP), Signal-to-Interference-plus-Noise Ratio (SINR), Reference Signal Received Quality (RSRQ) using the G-NetTrack Pro application, and throughput, delay, and packet loss using the Wireshark application. The results indicate that Telkomsel exhibited the most stable RSRP performance within the